Emotional Intelligence and Employee Performance in Nepalese Commercial Banks - Shrestha, Bikram Kumar (Nexus: Journal of Interdisciplinary Engineering, Technology and Management, 2026)
Emotional Intelligence has increasingly been recognized as a crucial predictor of workplace behavior and performance, especially in service-oriented industries such as banking. In Nepalese commercial banks, where employees frequently interact with clients and navigate high-pressure environments, EI may play a vital role in shaping employee outcomes. This study investigates the impact of three key dimensions of emotional intelligence: self-awareness, empathy, and stress management, on employee performance in Class ’A’ commercial banks in Nepal. It aims to identify which emotional competencies are most influential in enhancing workplace effectiveness. The study used a descriptive and explanatory research design and adopted a quantitative approach. Data were collected through structured questionnaires using a 5-point Likert scale, distributed to bank employees via Google Forms and print copies. Out of 600 distributed questionnaires, 398 valid responses were analyzed using SPSS and AMOS. Reliability, validity, and model fitness were assessed using composite reliability, AVE, and structural equation modeling. The findings reveal that empathy and stress management have significant positive effects on employee performance, while self-awareness does not show a statistically significant influence. Among the constructs, empathy emerged as the strongest predictor of employee performance, suggesting the importance of interpersonal sensitivity in the banking context. Emotional intelligence, particularly empathy and stress management, plays a significant role in shaping employee performance. However, self-awareness alone may not be sufficient to drive performance outcomes without supportive organizational or behavioral mechanisms. The results underscore the need for banks to integrate emotional intelligence training, especially in empathy and stress regulation, into employee development programs. Organizations should also consider emotional competence in recruitment and leadership development. This study provides novel insights into the domain-specific role of emotional intelligence in the Nepalese banking sector. It offers empirical evidence from a developing-country context, where such research remains relatively limited.